2019
DOI: 10.1016/j.seares.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Sabellaria spinulosa reefs in an intensively fished area of the Dutch Continental Shelf, North Sea

Abstract: The tube-building polychaete Sabellaria spinulosa (Ross worm) can form conspicuous biogenic reefs that stabilize the seabed and increase biodiversity by providing a habitat for a multitude of other species. These reefs, however, are assumed to be vulnerable to human-induced physical disturbances of the seabed. In the Greater North Sea, S. spinulosa reefs are recognized to be under threat and worthy of protection. In August 2017, three S. spinulosa reefs with a minimum extent of 1016 m 2 were discovered in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…Now we investigate to what extent MBES backscatter data can be used to classify the sediments over megaripples. This is of particular interest for detailed habitat mapping [34], engineering projects such as offshore wind farms or pipe laying [22], and for modelers of sand waves who study the morphology, hydrodynamics, and sand transport at the seafloor [1,24]. In the previous sections it is found that higher acoustic classes correspond to sediments with a larger proportion of coarse sediments in this study area.…”
Section: Classifying Sediments Over Megaripplesmentioning
confidence: 61%
“…Now we investigate to what extent MBES backscatter data can be used to classify the sediments over megaripples. This is of particular interest for detailed habitat mapping [34], engineering projects such as offshore wind farms or pipe laying [22], and for modelers of sand waves who study the morphology, hydrodynamics, and sand transport at the seafloor [1,24]. In the previous sections it is found that higher acoustic classes correspond to sediments with a larger proportion of coarse sediments in this study area.…”
Section: Classifying Sediments Over Megaripplesmentioning
confidence: 61%
“…2015) and sand banks (Van der Reijden et al . 2019), it has been shown that tube‐building worms are significantly more abundant in the troughs than on the crests, although it should be noted that the study by van der Reijden et al . (2019) focused on the tube‐building worm Sabellaria spinulosa .…”
Section: Discussionmentioning
confidence: 94%
“…2018; Van der Reijden et al . 2019). At the same time, benthos may modify their physical habitat (Eckman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Increase surface heterogeneity of the bottom and enlarges landscape complexity [45,46] Mediterranean Sea; Adriatic coast (Italy)…”
Section: Form Tubes With Terrigenous Particles and Can Build Reefs Inmentioning
confidence: 99%